2016
DOI: 10.1038/nenergy.2016.98
|View full text |Cite
|
Sign up to set email alerts
|

Path dependence in energy systems and economic development

Abstract: Energy systems are subject to strong and long-lived path dependence, due to technological, infrastructural, institutional and behavioural lock-ins. Yet

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 65 publications
1
81
0
1
Order By: Relevance
“…In other words, it is unlikely that either technology will meet the average duration of the innovation chain for successful Nuclear Electricity Coal Oil Gas Woodfuel Hydro Electricity Source: Fouquet (2009) energy transitions (although, SPVs may still do so, if they reach a share of 80% by 2050). However, it could be argued that because of the large number of inventions in energy technologies in the last 150 years, the strong path dependence in modern energy systems has delayed the uptake of certain technologies (Fouquet 2016a).…”
Section: The Speed Of Historical Energy Transitionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In other words, it is unlikely that either technology will meet the average duration of the innovation chain for successful Nuclear Electricity Coal Oil Gas Woodfuel Hydro Electricity Source: Fouquet (2009) energy transitions (although, SPVs may still do so, if they reach a share of 80% by 2050). However, it could be argued that because of the large number of inventions in energy technologies in the last 150 years, the strong path dependence in modern energy systems has delayed the uptake of certain technologies (Fouquet 2016a).…”
Section: The Speed Of Historical Energy Transitionsmentioning
confidence: 99%
“…However, successful uptake tended to depend on the co-evolution of technologies, industries and institutions that enabled new energy sources to emerge from niches and become core elements in the regime (Geels 2002, Foxon 2011. This allowed 'technological clusters' to dominate and ultimately create 'lock-ins' (Grübler et al 1999, Unruh 2000, Fouquet 2016a). …”
Section: Energy Transitions and Declining Industriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is suggested that the rate of adjustment to higher prices is dependent on the phase of economic development, and this implies that, after the initial phase of industrialisation, households and firms will be slower to invest in efficient technology as a result of higher energy prices. Using Acemoglu and Robinson's (2012) terminology, the process of industrialisation is a critical juncture in an economy's history, and the outcome of these private and public investments are likely to strongly influence the long run energy-intensity pathway of the economy (Fouquet 2016b).…”
Section: Policy Recommendation 3: Energy Service Policies In Periods mentioning
confidence: 99%